Das andere New York: Friedhöfe, Freiräume und Vergnügungen, 1790-1860 - Möller, Angelika (transcript, 2015)
How could a sleepy town become the city that never sleeps? »The other New York« is about a neglected period: the antebellum era. From a social and cultural history perspective, Angelika Möller discusses the development of New York from a small town to a metropolis in the time between the American Revolution and the Civil War. Taking contemporary discourses and cultural practices into account, she shows how places in the urban space were planned, built, inhabited, appropriated, celebrated, plundered, transformed, and discarded. This study directs our attention at unusual open spaces and open air recreation, and it negotiates their role in the metropolization of New York.